Couple wearing fur. - Sahl, Ted (photographer):::Creator::::::::::::
Bearded man with a cigarette in his mouth wearing a ten gallon hat and fur-like coat. Standing beside him and holding on to the man's arm is a female impersonators in a gown with a fur-like boa around the neck.